GPI Is a Prognostic Biomarker and Correlates With Immune Infiltrates in Lung Adenocarcinoma - Han, Jiahui; Deng, Xinzhou; Sun, Renhuang; Luo, Ming; Liang, Meng; Gu, Bing; Zhang, Te; Peng, Zhen; Lu, Ying; Tian, Chao; Yan, Yutao; Luo, Zhiguo (Frontiers in Oncology, 2021)
Background: Glucose-6-phosphate isomerase (GPI) plays an important role in the process of glycolysis and gluconeogenesis. However, the role of GPI in lung adenocarcinoma (LUAD) remains unclear. Methods: All original data were downloaded from TCGA and GEO databases and integrated via R 3.2.2. GPI expression was explored with the Cancer Genome Atlas (TCGA), GEO (Gene expression omnibus) and Oncomine databases. The correlations between GPI and cancer immune characteristics were analyzed via TIMER and TISIDB databases. GPI specific siRNAs were used to verify the role of GPI expression on cell proliferation and cell cycle distribution. Results: In general, GPI is predominantly overexpressed and with a reference value in the diagnosis and prognostic estimation in LUAD. The up-regulated GPI was associated with poorer overall survival, clinical stage, N stage and primary therapy outcome in LUAD. Mechanically, we identified a hub gene that included a total of 56 GPI-related genes, which were tightly associated with the cell cycle pathway in LUAD patients. Knockdown of GPI induced cell proliferation inhibition and cells cycle arrest. GPI expression was positively correlated with infiltrating levels of Th2 cells and Treg cells, on the contrary, it was negatively correlated with infiltrating levels of CD8+ T cells, central memory T cells, dendritic cells, macrophages, mast cells and eosinophils. GPI was negatively correlated with the expression of immunostimulators, such as CD40L, IL6R and TMEM173 in LUAD. Conclusion: GPI may play an important role in cell cycle, and can be used as a prognostic biomarker for determining prognosis and immune infiltration in LUAD.